Medical and geographical features of oncopathology in the population of Zaporozhye region - Oleksenko, L. M.; Bashchenko, E. V. (Запорізький державний медичний університет, 2022)
The purpose of the study: to study the medical and geographical features as a permanent factor, to assess their impact on oncopathology of the population.
Keywords: тези доповідей